Problems of effectıve applıcatıons of aır defense means agaınst aır target actıvatıng at low altıtudes - Gasanov, Arzuman; Guliyev, Anar; Hasanli, Rashad (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This paper examines the defeat of various types of air attack weapons, such as fighters, helicopters, cruise missiles, reconnaissance unmanned aerial vehicles, armed unmanned aerial vehicles, drones and kamikazes by air defense systems, taking into account their low-altitude operation. For this purpose, efficiency coefficients are determined that characterize the defeat of low-altitude air attack weapons by anti-aircraft missile systems, taking into account their tactical and technical characteristics. To solve the problem, the first party was considered to be air attack weapons, such as fighters, helicopters, cruise missiles, reconnaissance unmanned aerial vehicles, armed unmanned aerial vehicles, drones and kamikazes, and the second party was considered to be the S-125 2TM, BUK-MB, Barak-8, S-300 PMU2, TOR-M2KM, Patriot MIM-104, Panisir S-1, Nasams-III, Igla-S, Strela-10, OSA-AK(M) anti-aircraft missile systems. Therefore, a mathematical model of the problem was developed using game theory. The obtained problem was solved using the simplex method. It was determined that the TOR-M2KM anti-aircraft missile system, which is an air defense system for engaging low-altitude air attack weapons, can be used primarily against fighters, helicopters, unmanned aerial vehicles, armed unmanned aerial vehicles and unmanned aerial targets during combat operations. Of the air attack weapons, it is proposed to use cruise missiles first of all during combat operations, and kamikazes at the next stage. It is advisable to use the Barak-8 air defense system against cruise missiles. The obtained results can be used in planning the effective implementation of an air defense system against low-altitude air attack weapons.